2022
DOI: 10.1371/journal.pone.0269185
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin, blood urea nitrogen, and high chest CT score determines ICU admission in COVID-19 positive UAE patients: A single center retrospective study

Abstract: Coronavirus Disease (COVID-19) was declared a pandemic by WHO in March 2020. Since then, additional novel coronavirus variants have emerged challenging the current healthcare system worldwide. There is an increased need for hospital care, especially intensive care unit (ICU), for the patients severely affected by the disease. Most of the studies analyzed COVID-19 infected patients in the hospitals and established the positive correlation between clinical parameters such as high levels of D-dimer, C-reactive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Previous studies have also revealed that high BUN levels are correlated with poor prognosis in ICU patients 24 25 . As high BUN was also found to be related to the poor prognosis of patients with acute heart failure, acute respiratory disease syndrome, and hepatic decompensation 26 27 28 , BUN might reflect the degree of injury of multiple important organs, which were also an important risk factor of critically ill patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have also revealed that high BUN levels are correlated with poor prognosis in ICU patients 24 25 . As high BUN was also found to be related to the poor prognosis of patients with acute heart failure, acute respiratory disease syndrome, and hepatic decompensation 26 27 28 , BUN might reflect the degree of injury of multiple important organs, which were also an important risk factor of critically ill patients.…”
Section: Discussionmentioning
confidence: 97%
“…Although many patients with DKA are complicated with acute renal failure, dehydration is the most common state among patients with DKA due to hypovolemia and hypotension Accepted Manuscript also revealed that high BUN levels are correlated with poor prognosis in ICU patients [24,25]. As high BUN was also found to be related to the poor prognosis of patients with acute heart failure, acute respiratory disease syndrome, and hepatic decompensation [26][27][28], BUN might reflect the degree of injury of multiple important organs, which were also found to be an important risk factor of critically ill patients.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…[25–28] In hospitalized ICU patients, elevated BUN levels indicate impaired renal function and are associated with poor prognosis. [29]…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] In hospitalized ICU patients, elevated BUN levels indicate impaired renal function and are associated with poor prognosis. [29] For COVID-19, major risk factors reported previously include age, masculinity, obesity, smoking, and chronic comorbidities such as hypertension and diabetes. [30,31] In our study, we found that dead patients had a higher proportion of diabetes, lower hematocrit and calcium ion levels compared with survived patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation